KEWENANGAN PENYIDIK PEGAWAI NEGERI SIPIL DALAM PELAKSANAAN DAN PENEGAKAN UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS ANGKUTAN JALAN DI KECAMATAN MANDAU - Fazly Mahatma Putra Gautama Negara; Mexsasai Indra; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The Ministry of Transportation is an institution that has the authority to issue policies and / or legal rules governing transportation issues. Legal policies or rules that bind all parties involved in transportation activities. The Department of Transportation is an institution established under Decentralization. Decentralization here implies escape from the center. One example of the role of the Department of Transportation in maintaining the maintenance of an integrated traffic system is enforcement. Article 276 and 262 of Law Number 22 Year 2009 Road Traffic and Transportation. The purpose of this study, namely: first to determine the obstacles faced by the Office of Traffic and Road Transportation in the implementation and enforcement of the Act. the second is the efforts made by the Office of Traffic and Road Transportation in enforcing the Road Traffic Law and its solutions.This type of research used in writing this thesis proposal uses the method of sociological legal research, because in this study the authors directly conduct research at the location or place of study in order to provide a complete and clear picture of the problem under study. This research is precisely in the office of the Regional Technical Implementation Unit of the Transportation Office of Mandau District, Bengkalis Regency. While the population and sample are all parties related to the problem examined in this study. Sources of data used, primary data, secondary data and tertiary data, data collection techniques in this study are observation, interviews and literature studies.From the results of this study it can be concluded that there are two main problems, namely: first, to find out the obstacles faced by the Office of Traffic and Road Transportation in the implementation and enforcement of articles 262 and 276 of Law Number 22 Year 2009 concerning Traffic and Road Transportation. That the applicable regulations are not adhered to, as well as overlapping authority between the transportation department of the Mandau sub-district and the Mandau district police. second, the efforts made by the Traffic and Road Transportation Agency in enforcing the Road Traffic Law by giving strict sanctions to road transporters who commit violations in the form of revoking route licenses, speeding tickets and imposing vehicles. The author's advice, firstly in order to be able to walk properly the importance of public vehicles entering the terminal, it requires strict sanctions for owners of public vehicles and also needed socialization about the authority of the transportation department in cracking down on road transport that commits traffic violations and the function of the terminal itself secondly, it is expected that the authorities related to cooperating in their respective portion and authority for the sake of creating smoothness, security, and order in traffic on the highway.Keywords: Authority - Road traffic and transportation - Non-motorized vehicles